Analytical and stochastic modeling techniques and applications : 19th International Conference, ASMTA 2012, Grenoble, France, June 4-6, 2012. Proceedings - Fiems, Dieter; Vincent, Jean-Marc; Al-Begain, Khalid (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 19th International Conference on Analytical and Stochastic Modelling Techniques and Applications, ASMTA 2012, held in Grenoble, France, in June 2012. The 20 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on queueing systems; networking applications; Markov chains; stochastic modelling.